Contested Spaces, Common Ground : Space and Power Structures in Contemporary Multireligious Societies. - Winkler, Ulrich. (Currents of Encounter, 2016)
Spaces are produced and shaped by discourses and, in turn, produce and shape discourses themselves. 'Space' is becoming a significant and complex concept for the encounter between people, cultures, religions, ideologies, politics, between histories and memories, the advantaged and the disadvantaged, the powerful and the weak. As a result, it provides a rich hermeneutical and methodological inventory for mapping interculturality and interreligiosity. This volume looks at space as a critical theory and epistemological tool within cultural studies that fosters the analysis of power structures and the deconstruction of representations of identities within our societies that are shaped by power.